Pengaruh Citra Merek, Kualitas Produk, Word Of Mouth Terhadap Keputusan Pembelian Tas Merek Eiger (Studi pada Konsumen Eiger di Kota Pontianak) - admin, SUCI IRMAJAYANTI B11112143 (Jurnal Manajemen Update, 2016)
Competiton beetwen manufacturers of bags is increasing and growing, so that producers should always produce the products which is update in order to seize and retain customers. In this case the company should really pay attention to the image products offered to consumers and always pay attention to the quality of each product to be produced so that consumers who were satisfied in purchasing products that provide positive word of mouth to other potential consumes. This study aimed to analyze whether the variables of the brand image, quality of product, eord of mouth, and have impact on the customer purchase decision toward product bags Eiger. This study was designed as an explanatory study. Population of the study was customers of product Tupperware in Pontianak. The sampling technique used was purposive sampling, namely 100 respondents as the total number of samples in Pontianak city. The analysis technique used was validity test, reliability test, classic asumption test, regression test, t test, f test, R2 test and detremination R analysis using SPSS version 22.0. the result of data analysis showed that the brand image, quality of product, word of mouth, both partially and simultaneously, have positive and significant impact on customer purchase decision toward product bags Eiger in Pontianak city with a significance value of 0.000 and R2 value of 55.5% while the remaining 44.5% are the other factors which were not investigated in this study. Keywords: Brand Image, Quality Of Product, Word Of Mouth, and Purchase Decision